Effectiveness of Individual Performance Dialogue on Employee Performance (Case Studies on Civil Servants of the Ministry of Finance in City of Semarang) - Sudiarti, Ni Made Watimena; Noersasongko, Edi; Pramudi, Yuventius Tyas Catur (Jurnal Penelitian Ekonomi dan Bisnis, 2021)
Bureaucratic Reform in human resources began with the birth of Law No. 5 of 2014 on State Civil Apparatus (ASN). The new paradigm in the ASN Law makes ASN employees a profession that has an obligation to conduct self-development and must take responsibility for performance and apply merit principles in the implementation of ASN management. The Ministry of Finance followed up the Bureaucratic Reform in hr with performance management policies. Performance management in the Environment of the Ministry of Finance consists of three main stages, namely planning, monitoring, and determining performance results and evaluation.  Performance evaluation results determine the performance value of employees and organizations, which affects employee careers and compensation. The solution by the Ministry of Finance is to implement management practices called Organizational Performance Dialogue (DKO) and Individual Performance Dialogue (DKI) whose main purpose is to improve the performance of employees and organization. This research is explanatory, where the research method used is Partial Least Square (PLS), with software for analysis using SmartPLS. Data collection instruments using questionnaires and structured interviews with research respondents are employees of the Ministry of Finance in Semarang City area. This research aims to know the effectiveness of performance dialogue on employee performance, so that the results are expected to be a reference in management practices in organizational units in the environment of the Ministry of Finance in an effort to improve the performance of employees and organizations. Keywords:Effectiveness, Individual factors, Leadership factors, Performance dialogue, Employee performance